DOES THE SYNECTIC LEARNING MODEL STATISTICALLY ENHANCE THE VOCATIONAL STUDENTS' WRITING SKILLS? - Dhita, Ferlin Ayp; Pohan, Albert Efendi; Shalehoddin, Shalehoddin; Adam, Adam (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
Proficiency in English communication is a critical skill that requires continuous improvement, as it is one of the essential competencies demanded by the professional work of the world and must be mastered by vocational school students. Among these competencies, one of the required abilities is to compose a cover letter for job applications, which is particularly significant. Writing proficiency encompasses an individual's capacity to articulate ideas, concepts, and opinions using appropriate language. However, vocational school students in Batam City continue to experience difficulties in composing application letters in English. This study aims to quantitatively assess the implementation of the synectic learning model in Batam City Vocational Schools. To achieve this objective, researchers conducted an experimental study at SMK Globe National Plus 2 Batam, involving 80 participants. The requisite research data were collected through written assessments and statistically analyzed using SPSS Version 20. The findings indicated that the implementation of the synectic learning model can enhance students' ability to compose application letters. Consequently, the results of this research contribute to the implementation of the synectic learning model in vocational schools in Batam City, with the goal of increasing the preparedness of vocational school graduates for entry into the professional and industrial sectors.